PELATIHAN PEMBUATAN SIRUP JAHE DALAM USAHA MENCIPTAKAN NILAI TAMBAH TANAMAN JAHE MASYARAKAT - Emi Roslinda; Tri Widiastuti; Azzania Abidatin Nurul Khumsyah; Utari Nurfatimah; Windi Karlindasari; Dhea Ananda Syasabila (JMM (Jurnal Masyarakat Mandiri), 2022)
Abstrak: Jahe (Zingiber officinale) adalah salah satu hasil pertanian unggulan di Desa Pasir Palembang Kecamatan Mempawah Timur, Kabupaten Mempawah, Kalimantan Barat, yang masih dijual mentah dengan harga yang sangat murah karena pandemi Covid-19 yang masih terjadi saat ini. Kegiatan pengabdian ini dimaksudkan untuk mendiseminasikan produk olahan jahe agar pemanfaatan jahe menjadi optimal dan nilai ekonomisnya meningkat. Metode yang diterapkan adalah: pemaparan materi, diskusi, pembuatan sirup jahe serta teknik pasteurisasi untuk pengemasan dengan teknik sederhana. Mitra kegiatan adalah 25 orang ibu-ibu PKK. Kegiatan PKM ini telah meningkatkan pengetahuan dan keterampilan peserta dalam mengolah jahe menjadi sirup, terutama dalam pengemasan secara pasteurisasi meningkat 100%. Hasil pelatihan menunjukkan semua anggota kelompok PKK mempraktikkan secara aktif setiap tahap pembuatan dan pengemasan sirup jahe. Sejalan dengan program peningkatan nilai tambah hasil pertanian, para wanita yang tergabung dalam anggota kelompok PKK Desa Pasir Palembang dapat menerapkan teknik pengolahan jahe untuk meningkatkan pendapatan keluarga.Abstract: Ginger (Zingiber officinale) is one of the leading agricultural products in Pasir Palembang Village, East Mempawah District, Mempawah Regency, West Kalimantan, which is still sold raw at a meager price due to the current Covid-19 pandemic. This service activity is intended to disseminate ginger processed products so that the utilization of ginger becomes optimal and its economic value increases. The methods applied are material presentation, discussion, making ginger syrup, and pasteurization techniques for packaging with simple techniques. The partners of this activity are 25 PKK mothers. This PKM activity has increased the knowledge and skills of PKK mothers in processing ginger into syrup, especially in pasteurisasi process increase 100%. The members of the PKK group seemed enthusiastic about understanding the training materials and eager to practice each stage of making and packaging ginger syrup directly. In line with the increase in added value of agricultural products program, it is hoped that the women who are members of the PKK Desa Pasir Palembang can apply the ginger processing technique to increase family income through this activity. Ginger (Zingiber officinale) is one of the leading agricultural products in Pasir Palembang Village, East Mempawah District, Mempawah Regency, West Kalimantan, which is still sold raw at a meager price due to the current Covid-19 pandemic. This ginger activity is to disseminate processed products so that their utilization is optimal and their economic value increases. The methods applied are material presentation, discussion, making ginger syrup, and pasteurization techniques for packaging with simple techniques. The activity partners are 25 PKK women. This PKM activity has increased the knowledge and skills of participants in ginger into syrup, especially in processing it through pasteurization, rising by 100%. The training results showed that all members of the PKK group looked enthusiastic about understanding the training material and excited to practice each stage of making and packaging ginger syrup. With the program to increase the added value of agricultural products, through this activity, it is hoped that women who are members of the PKK group in Pasir Palembang Village can apply ginger processing techniques to increase family income.